Konsep Uang dalam Persfektif Ekonomi Islam - Bunga Agustina; Muhammad Aditya Sundawa; Al Fatih Faiz Fahlevi; Reni Ria Armayani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The concept of money in Islamic economics is grounded in the understanding that money is not merely a medium of exchange but a trust that must be managed according to the principles of justice, benefit, and ethical conduct. In this perspective, money cannot be treated as a commodity traded solely for profit without supporting real economic activities, making practices such as usury (riba), excessive uncertainty (gharar), and hoarding incompatible with Islamic values due to their potential to create inequality and economic instability. Islamic economics emphasizes that the circulation of money must be connected to the real sector to generate added value and support sustainable economic growth. Furthermore, the management of money aims to promote fairness and social balance through mechanisms such as zakat, infaq, and charity. Thus, the Islamic view of money provides an ethical foundation and practical framework for developing a financial system that is stable, inclusive, and oriented toward societal well-being.